Characteristics of preeclampsia cases based on early-onset and late-onset preeclampsia at Batuyang Primary Health Center in 2022–2024 - Wirananda, I Made Surya Vedo; Putra, Dewa Made Sucipta (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2025)
Introduction: Preeclampsia remains one of the leading causes of maternal and neonatal morbidity and mortality in Indonesia, with a significant incidence during pregnancy. It is classified into early-onset preeclampsia (EOPE) and late-onset preeclampsia (LOPE) based on the gestational age at the time of diagnosis, each characterized by distinct clinical presentations and etiological mechanisms. This study aims to compare demographic and clinical characteristics between early-onset pre-eclampsia (EOPE) and late-onset pre-eclampsia (LOPE) at PKM Batuyang during the period 2022–2024. Methods: This study employed a retrospective cross-sectional design with non-probability sampling. Data were obtained from the medical records of preeclamptic patients treated at Batuyang Primary Health Center between 2022 and 2024. The analyzed variables included maternal age, gestational age, parity, body mass index (BMI), history of abortion, hypertension, diabetes mellitus, and multiple pregnancies. Results: Among the 162 preeclampsia cases reviewed, LOPE was more prevalent (84.6%) compared to EOPE (15.4%). Most cases occurred in women aged ≥35 years and those with multiparity. The majority of patients had a BMI below 30 kg/m². A small proportion of patients had a history of chronic hypertension, diabetes mellitus, or multiple gestation. Conclusion: Late-onset preeclampsia was more frequently observed than early-onset cases at Batuyang Primary Health Center. Classification based on onset time is essential to guide optimal clinical management strategies. Further research is needed to identify risk factors to improve early detection and management of pre-eclampsia, thereby potentially reducing maternal and infant morbidity and mortality rates.